Designing interactive newsprint. Issue 104 (August 2017) - Frohlich, David M.; Ely, Philip; Moore, Helen; Golsteijn, Connie; Egglestone, Paul; Mills, John; Rogers, Jon; Metcalf, Tom; Stone, Kate; Menicou, Maria
Abstract: The possibility of linking paper to digital information is enhanced by recent developments in printed electronics. In this article we report the design and evaluation of a local newspaper augmented with capacitive touch regions and an embedded Bluetooth chip working with an adjunct device. These allowed the interactive playback of associated audio and the registration of manual voting actions on the web. Design conventions inherited from paper and the web were explored by showing four different versions of an interactive newspaper to 16 community residents. The diverse responses of residents are described, outlining the potential of the approach for local journalism and recommendations for the design of interactive newsprint. Highlights: Interactive newsprint can be authored to include audio information and voting. Interactive paper can be designed and experienced at four different levels. Audio can add personality and authenticity to printed news. Printed and online news might be combined in new ways through interactive newsprint.